Třikrát Rhees (Wittgenstein): Rush Rhees: Wittgenstein on Language and Ritual, In: McGuinness, B. (ed.): Wittgenstein and his Times, Thoemmes Press, Bristol, 1982, str. 69–107. Původně in: Essays on Wittgenstein in Honour of G. H. von Wright (Acta Philosophica Fennica, 28); Rush Rhees: ‚Ontology‘ and Identity in the Tractatus a propos of Black‘s Companion, In: Rush Rhees: Discussions of Wittgenstein, Thoemmes Press, Bristol 1970, str. 23–36. Původně in: Studies in the Philosophy of Wittgenstein, Routledge, 1969; Rush Rhees: Wittgenstein’s Builders, In: Rush Rhees: Discussions of Wittgenstein, Thoemmes Press, Bristol 1970, str. 71–84. Původně in: Proceedings of the Aristotelian, Society, 1959–1960 - Holeček, Tomáš (Lidé města, 2005)
A review of the books by Rush Rhees.